(untitled) (Research, Society and Development, 2021)
Microbial activities in the soil are important indicators of changes caused by agricultural practices, being responsible for physical, chemical and biological changes in organic residues, which affect soil fertility. The objective was to evaluate the microbial activity present in the soil in a management system intercropped with legumes, fruit trees and forest essence in comparison with an area of ​​native forest. The work was developed at the Federal Institute of Science and Technology of Roraima - Campus Novo Paraíso, in three areas, intercropping system of gliricidia + fruit trees (orange and banana), without gliricidia (orange and forest essentials) and native forest. Soil samples were collected at a depth of 0 cm - 10 cm and 10 cm-20 cm, placed in a thermal box and kept at 4 ºC. Soil Microbial Biomass Carbon (BMS-C), Soil Microbial Biomass Nitrogen (N-mic) and microorganism population (total, cellulite, ammonifiers and actinobacteria) were analyzed. The area of ​​the intercropping of gliricidia + fruit trees (orange and banana) had a greater population of microorganisms and an increase of 356% in microbial biomass carbon, proving to be an alternative system for the intercropping of plant species, favoring the supply of nutrients for the plants.